2021
DOI: 10.1038/s41419-021-04087-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal transfer of tumor-associated macrophage-derived hsa_circ_0001610 reduces radiosensitivity in endometrial cancer

Abstract: The occurrence of radioresistance is a clinical obstacle to endometrial cancer (EC) treatment and induces tumor relapse. In this study, we found that tumor-associated macrophages (TAMs) enriched in EC specimens were determined to present an M2-like phenotype. In vitro, the coculture of M2-polarized macrophages significantly downregulated the radiosensitivity of EC cells by releasing exosomes. Hsa_circ_0001610 was found to be abundant in exosomes derived from M2-polarized macrophages (EXOs), and hsa_circ_000161… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…The knockdown of has_circ_0001610 in in vitro and in vivo results in the increased radiosensitivity of EC. This study showed that knowledge about complicated miRs machinery in macrophages could help to increase cancer sensitivity to therapies, e.g., radiotherapy [ 135 ].…”
Section: Promising Therapiesmentioning
confidence: 99%
“…The knockdown of has_circ_0001610 in in vitro and in vivo results in the increased radiosensitivity of EC. This study showed that knowledge about complicated miRs machinery in macrophages could help to increase cancer sensitivity to therapies, e.g., radiotherapy [ 135 ].…”
Section: Promising Therapiesmentioning
confidence: 99%
“…The administration of exosomes in a xenograft EC model caused a post-irradiation increase in tumor growth and promoted EMT. These effects were augmented with the administration of exosomes that overexpressed hsa_circ_0001610, whereas the silencing of hsa_circ_0001610 abolished the ability of the delivered exosomes to weaken the radiosensitivity of EC cells [ 59 ]. Another recent study provided additional evidence demonstrating that TAMs promote the proliferation of EC cells and EMT via exosome transfer.…”
Section: Exosomes In the Pathophysiology Of Endometrial Cancermentioning
confidence: 99%
“…Cyclin B1, a key mitotic cyclin, is a downstream target of hsa_circ_0001610/miRNA-139-5p axis. After the transfer of hsa_circ_0001610 by M2-sEVs to endometrial cancer cells, cyclin B1 expression is upregulated through miRNA-139-5p, which affects the G2/M phase of the cell cycle, when the cells are the most sensitive to radiation, reduces the radiosensitivity of endometrial cancer cells, and affects prognosis ( Gu et al, 2021 ) (see Table 2 ). This will provide new targets for enhancing the radiosensitivity of EC cells in clinical settings.…”
Section: Role Of M-sevs In Cancermentioning
confidence: 99%